Oil slick monitoring using Sentinel-I SAR images - Rodrigues, Tomás (2021)
This paper presents an algorithm developed in the context of an undergraduate degree of Informatics Engineering for the detection of oil slicks in images from a Synthetic Aperture Radar (SAR). Oil slicks represent a serious threat to the marine ecosystem in the coastal areas and SAR images have been increasingly used in the supervision of this environmental disaster, due to its numerous advantages when compared to images in the visible domain. The developed algorithm envisages simplicity and computational efficiency and is divided in four phases: land masking, statistical analysis of sea, detection of suspected oil slick locations, and final validation. The usage of amplitude SAR images, instead of Single Look Complex (SLC) ones, contributes to the overall low computational requirements. The obtained results are encouraging for real-world applications.